Analisis Status Gizi Anak Usia Di Bawah Dua Tahun (Baduta) Pada Program Jaring Pengaman Sosial Bidang Kesehatan (JPS-BK) - Diah Krisnatuti; Hidayat Syarief; Soekirman Soekirman; Hardinsyah Hardinsyah; Asep Saefuddin (Media Gizi dan Keluarga, 2006)
The objective of this research was to analyze the influence of the Social Safety Net-Health Sector Program (JPS-BK) on growth of under-two year children (baduta). The study was carried out in Kebumen, Purworejo and Sukohatjo of Central Java, and Lombok Timur and Sumbawa of West Nusa Tenggara. This study was designed as cross sectional with Posttest-Only Nonequivalent Group Study Design, This was applied considering the data was collected in a moment just afier JPS-BK program has been starting with two nonequivalent groups (one was target group and another was non target group of JPS-BK). The sample was mothers who had breast-feeding status and had been pregnant between October 1998 and ended in 2000. Total sample was 622 mothers, consisted of 544 mothers of JPS-BK and 118 mothers of Non JPS-BK. Growth of baduta of JPS-BK was not dgiterent from baduta of Non JPS-BK. Nutritional status of baduta (W/A) had positive and significant correlation with birth weight, immunization, and complementary feeding (MP-AS1 JPS-BK). Nutritional status of baduta (H/A) had positive and significant correlation with birth weight, MP-AS1 JPS-BK. immunization and mother's educational level. Nutritional status of baduta (W/H) had positive and significant correlation with birth weight, MP-ASI JPS-BK, immunization, income per capita, and mother's educational level.